STRATEGI KPU KABUPATEN JOMBANG MENINGKATKAN PARTISIPASI POLITIK PEMILIH PEMULA PADA PEMILIHAN UMUM TAHUN 2024 - Laila, Fitria Nur; Iman Pasu Marganda Hadiarto Purba (Kajian Moral dan Kewarganegaraan, 2024)
Indonesia is a democratic country where the people hold supreme power. The means of popular democracy are realized in elections which are related to political participation, the higher the participation is directly proportional to the success of the election. The voter category that dominates the 2024 election is first-time voters. Jombang Regency experienced an increase in the political participation of first-time voters by 14%. The aim of this research is to determine the Jombang KPU's strategy to increase the political participation of first-time voters in the 2024 election. Chandler's strategy theory is used with 3 stages of formulation and long-term targets, action selection, resource allocation. Using qualitative methods, qualitative descriptive research design. The snowball sampling technique was used with 1 Key Informant, namely the Chair of the Jombang KPU. research location at the Jombang KPU office. Data collection techniques include observation, interviews, documentation. The research results found that the Jombang KPU strategy increased the political participation of novice voters through 2 methods, namely socialization and voter education. Socialization in 2 ways, direct and indirect. directly through ball pick-up agendas, discussions, seminars, lectures, simulations, talk shows. indirectly through Electronic Mass Media, Socialization Materials, Socialization Props, Utilization of Popular Culture, local, KPU pages, Notice Boards, Social Media, Film Creation Media. Voter education is carried out using election materials. Based on Chandler's strategy theory, the most influential stage in increasing participation is action selection. Socialization activities using various methods and voter education to build voter knowledge can increase participation. The Jombang KPU should continue to form democracy volunteers as an optimization strategy.